Child Maltreatment Victimization and Subsequent Perpetration of Young Adult Intimate Partner Violence: An Exploration of Mediating Factors. (May 2013) - Millett, Lina S.; Kohl, Patricia L.; Jonson-Reid, Melissa; Drake, Brett; Petra, Megan
This study examined whether young adults with documented histories of child maltreatment had higher records of documented severe intimate partner violence (IPV) perpetration than an income-matched control group. It also examined whether this association was mediated by juvenile violent delinquency, problematic substance use, or mental health problems. Study data came from one state's administrative public sector records of child welfare, juvenile court, mental health, income maintenance, and birth records. The study employed a prospective longitudinal design to follow children for 16 years ( N = 5, 377). The IPV was measured by police arrests and temporary restraining order petitions. Multiple group path analysis was used to examine mediation hypotheses and determine whether they differed by gender. The study found that IPV perpetration rates were higher among maltreated than control participants and higher in maltreated men than in women. For men, maltreatment had both direct and mediated effects on IPV perpetration through violent delinquency. For women, maltreatment did not directly or indirectly predict IPV perpetration, though low power makes these findings tentative. The study highlights the importance of child maltreatment prevention as a way to reduce violence later in life and suggests that the juvenile justice system may also provide a point of intervention for the maltreated youth.